Innovation in university science teaching through professional learning communities - Soraya Elena Layton Jaramillo; Oscar Germán Duarte Velasco; Eva María Aguaded Ramírez; Francisco Javier Carrillo Rosúa (Journal of Technology and Science Education)
This paper analyzes the relationship between the development of pedagogical innovation projects in experimental sciences and the establishment and evolution of Professional Learning Communities (PLC) in higher education, within an open innovation framework. To achieve this, an evaluative study employing a mixed-methods approach was conducted, involving 93 members of the academic community—including faculty, students, alumni, and administrative staff—who collaboratively designed and implemented 15 pedagogical innovation projects across various scientific disciplines. The findings indicate that projects with a clearly defined pedagogical objective foster dialogue, reflection, collaborative work, and mutual learning, thereby facilitating the formation and evolution of PLC. In conclusion, open innovation and PLC contribute to transforming a culture of individualism into one of collaboration, ultimately enhancing the quality of higher education.